2007
DOI: 10.1002/jsl.42
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermal stability of perfluoropolyalkylethers (PFPAEs)

Abstract: End-group modifi cation of poly(hexafl uoropropylene oxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…6a, b ), and the maximum degradation rate is around 200 °C. It was demonstrated that a facile and severe thermal degradation of PFPAE components can occur in the presence of Lewis acid (such as AlF 3 ) [ 60 ] or even in presence of Al 2 O 3 [ 61 ]: in these conditions, a complete degradation of fluorinated chains occurs above 180 °C [ 60 , 61 ]. In our case, as the cationic polymerization requires the formation of superacids [ 1 ] that can still be present in the photocured networks, the thermal stability of the PFPAE-based copolymers has been adversely affected.…”
Section: Resultsmentioning
confidence: 99%
“…6a, b ), and the maximum degradation rate is around 200 °C. It was demonstrated that a facile and severe thermal degradation of PFPAE components can occur in the presence of Lewis acid (such as AlF 3 ) [ 60 ] or even in presence of Al 2 O 3 [ 61 ]: in these conditions, a complete degradation of fluorinated chains occurs above 180 °C [ 60 , 61 ]. In our case, as the cationic polymerization requires the formation of superacids [ 1 ] that can still be present in the photocured networks, the thermal stability of the PFPAE-based copolymers has been adversely affected.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism of CF 3 COF release during the first stage of decomposition is still not clear, , it is generally believed that the oxide surface is slowly fluorinated by a nucleophilic substituted CF 3 COF followed by a second stage where the rapid decomposition of PFPE commences via a chain reaction catalyzed by freshly formed strong Lewis acid (FeF 3 ) sites, resulting in complete fluorination and decomposition of PFPE fluids into volatile perfluorocarbons, carbonyl fluoride, oxidized products, and hydrogen fluoride if any water is present. Much of the documented literature reports that the majority of the second-stage byproducts are (CF 3 ) 2 CO and low molecular weight Krytox chains but other degradation mechanisms cannot be completely dismissed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the mechanism of CF 3 COF release during the first stage of decomposition is still not clear, 54,55 it is generally believed that the oxide surface is slowly fluorinated by a nucleophilic substituted To obtain mechanistic insights into the metal fluoride formation, all the volatile chemical species generated during heat treatment were analyzed using mass spectrometry (MS). The presence of COF is due to ionization of COF 2 produced by oxidation of trifluoroacetyl fluoride and hexafluoroacetone, whereas CF 3 is from ionization of C 2 F 6 released by thermal decomposition of hexafluoroacetone or trifluoroacetyl fluoride.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
“…3a, b). The PFPAE thermal degradation may be triggered by the presence of Lewis acids such as AlF 3 [77] or Al 2 O 3 [78] and can result in a complete loss of the fluorinated segments above 180°C. Moreover, the thermal behavior could be adversely affected by residues of the superacids generated during the photoinitiation of the cationic polymerization and still present in the network.…”
Section: Photopolymers Characterizationmentioning
confidence: 99%